Peramalan Produksi Kedelai di Provinsi Nusa Tenggara Barat menggunakan Model Grey-Markov (1,1) - Nurmaulia, Ananda Rizantia; Harsyiah, Lisa; Purnamasari, Nur Asmita; Jurniati, Jurniati (Program Studi Matematika, 2025)
The continuously increasing soybean imports are caused by the imblance in domestic soybean produstion. This indicates that nationalsoybean self-sufficiensy has not yet been achieved, as many soybean farmlands have now been converted to other commodities. This condition occurs in West Nusa Tenggara, Which is one of Indonesia’s nationalsoybean production centers. To understand future soybean production conditions, forecasting future soybean production in West Nusa Tenggara province using the grey_markov (1, 1) model. This model only requires minimal data for forecasting, which aligns with the limites research data available. The data used in this study is soybean production data from West Nusa Tenggara province. The research results show that in 2022, soybean production in West Nusa Tenggara province will decline, with the prediction demonstrating good accuracy as indicated by a MAPE value of 15.75%.